Dynamics and Challenges of Democracy in Local Elections in Indonesia and the Netherlands - Hargono, Hargono; Rustan, Ahmad; Jambak, Fachmi; Alba, La Ode; Rahman, Rofi Aulia (SASI, 2024)
Introduction: Elections for regional heads and heads of government are one of the important aspects in building a democratic system that encourages citizen participation in the political process.Purposes of the Research:  This study aims to describe the dynamics and challenges of democracy associated with the implementation of regional elections in several countries. Local elections are a major test of a country's democratic health, and a variety of factors can affect the outcome and integrity of the process.Methods of the Research: This research is legal research using two legal approaches, namely the statute approach and the comparative approach.Results of the Research: The results showed that regional elections have complex dynamics and several significant challenges in the context of democracy. These dynamics include intense political competition, increased public participation, and changes in political communication through social media. While the challenges that need to be faced in regional elections include contests involving incumbents, fraud in elections, political money, voter participation, political polarization, and the integrity of organizers that occur in Indonesia and in the Netherlands. Thus, this study shows that regional elections are not only a political event, but also a test of the quality of a country's democracy. Concerted efforts to address these challenges will play a key role in maintaining and strengthening democratic systems that are healthy and responsive to people's needs.